The Law of Genre: Derrida and Blanchot - Llevadot, Laura (Escritura e Imagen, 2023)
The aim of this paper is to demonstrate Derrida’s contributions to gender theory based on the analysis of his reading of Blanchot’s work La foile du jour. To this end, the context of the appearance of this analysis in the Seminar on gift (Donner le temps, II) will be analyzed, its relationship with the question of the story (récit) and the gift, as well as the figures of double invagination, incest, the law and the norm. The final purpose of the article is to show, based on Derridean analysis of Blanchot’s text, a modality of subversion of the law of genre that exceeds, and complements, that proposed by Butler based on Kafka’s story Before the Law.
Keywords: Gender; story (récit); Derrida; Blanchot; Butler; law; norm